Analysis of Indonesia's Economic Growth Sources (Study 1998-2006) - Anik Hariyati (TRIGIN PUBLISHER, 2020)
This paper attempts to describe the sources of Indonesia's post-crisis economic growth (1998) up to the end of the analysis period (2006). The methodology used is qualitative and quantitative description. The quantitative approach is carried out in the form of calculations in a systematic formulation that focuses on hypothesis testing, while the qualitative approach is carried out by studying literature and accompanied by data analysis. The observed variables include domestic and foreign investment, exports and imports and foreign debt. The results showed that during the post-crisis period until 2006 the variables of domestic investment, exports and imports had a positive effect on economic growth. Meanwhile, the foreign investment variable, foreign debt, which should have had a positive impact on economic growth, turned out to be the opposite, this was because foreign investors brought most of their profits back to their country. Meanwhile, foreign debt provides a large burden because of the interest and installments.